Regional Anesthesia for Acute Pain Treatment in Pre- Hospital and In-Hospital Emergency Medicine. - Fichtner, Andreas (Deutsches Ärzteblatt International, 2023)
Background: More than half of all emergency department patients seek help for acute pain, which is usually of musculoskeletal origin. Acute pain is often inadequately treated even today, particularly in children and in older patients. In this study, we assess the potential role of regional anesthetic methods in improving the treatment of pain in the preclinical and clinical emergency setting. Methods: Pain-related reasons for admission were identified and quantified from emergency admission data. A structured literature search was carried out for clinical studies on the treatment of pain in the emergency setting, and a before-and-after comparison of the pain relief achieved with established vs. newer regional anesthetic methods was performed. Results: 43% of emergency patients presented with acute musculoskeletal pain. The literature search yielded 3732 hits for screening; data on entity-specific pain therapy spectra were extracted from 153 studies and presented for the main pain regions. The degree of pain relief obtained through regional anesthetic procedures, on a nominal rating scale from 0 to 10, was 4 to 7 points for acute back and chest wall pain, >6 for shoulder pain, 5 to 7 for hand and forearm injuries, and >4 for hip fractures. These results were as good as, or better than, those obtained by analgesia/sedation with strong opioids. Conclusion: Modern regional anesthetic techniques can improve acute pain management in the emergency department and, to some extent, in the pre-hospital setting as well. Pain relief with these techniques is quantifiably better than with strong opioids in some clinical situations; moreover, there is evidence of further advantages including process optimization and fewer complications. Data for comparative study remain scarce because of a lack of standardization.